Pengaruh Sistem Reward Dan Punishment Terhadap Kinerja Karyawan - Bagas Arif Prabaswara; Elsa Anggraeni Piliyanto (Global Leadership Organizational Research in Management, 2024)
The purpose of the scientific article entitled "The Influence of the Reward and Punishment System" is to conduct a literature review with the aim of conducting an investigation into the influence of the reward and punishment system on employee performance. In addition, it is very important to formulate hypotheses regarding the influence of each variable that will be used for further research on the topic of sustainability in the field of Human Resource Management. The method used in the process of writing this article is known as qualitative research, which includes library research, drawing from internet sources such as Google Scholar, relevant journals and articles, and the use of the Mendeley application for the compilation of bibliographic references. The following are the conclusions that can be drawn from this article: The performance of employees in the performance of this system is very positive and significant. 2) Employee punishment is better than facing employee performance. 3) the tax and legal system has a positive and statistically significant effect on employee performance.